Analisis Pemanfaatan WhatsApp sebagai Sarana Percepatan Pelayanan Administrasi Kependudukan di Kantor Desa Tebel - Indi Aulia Ali; Lintang Cyta Damayanti; Roudhotul Jannah; Anis Koirunnisak; Endar Bahtiar; Iva Inayatul Ilahiyah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This research aims to describe the use of WhatsApp social media as a means of population administration services at the Tebel Village Hall, Bareng District. The problem raised in this research is the process of using WhatsApp in services and how the public responds to this service. This research uses a qualitative descriptive approach with data collection techniques in the form of in-depth interviews and observations of officers and service users. The research results show that using WhatsApp helps speed up communication, makes sending required documents easier, and provides more practical access to information for village communities. Village officials are also able to provide more responsive service assistance. However, several obstacles were also found, such as limited number of officers and technical problems with the system. The results show that digital media such as WhatsApp can help make public services more accessible, especially in rural areas. This study found that WhatsApp was well received by the public and helped administration.